DROPLET SPECTRA AND SURFACE TENSION OF SPRAY SOLUTIONS BY BIOLOGICAL INSECTICIDE AND ADJUVANTS - Costa,Lilian L. (2017)
ABSTRACT Biological insecticides can be another pest control method used in integrated pest management; hence there is a demand for scientific information about these products to understand the appropriate application technique. The aim of this study was to evaluate the spray spectra data by different nozzle types using biological insecticide isolated and with adjuvants, as well the surface tension of these spray solutions. For droplet spectra data, a particle size analyzer was used and for surface tension of the spray solution, the method of pendant drop was used. Among the nozzles tested, ADI 11002 provided greater droplets median diameter volume, a lower percentage of droplets with diameters less than 100 μm and also the highest coefficient of uniformity. In general, the addition of adjuvants reduced the median droplet diameter and increased the proportion of drops susceptible to spray drift. By adding adjuvants to the spray solution there was a lower surface tension, which were dependent of the adjuvant chemical group. The Silwet L-77® adjuvant showed the lowest surface tension among the spray solutions evaluated.